2019
DOI: 10.3390/su11061769
|View full text |Cite
|
Sign up to set email alerts
|

Brand Revitalization of Heritage Enterprises for Cultural Sustainability in the Digital Era: A Case Study in China

Abstract: Many heritage enterprises have been struggling with severely declining brands in the digital era and are in desperate need of brand revitalization. Resolving the decline of heritage brands is not only a commercial issue but also a cultural sustainability issue because a living heritage brand can be considered an example of the preservation and even inheritance of a certain culture or history. While the prior literature has largely overlooked the cultural dimension of sustainability and the management of herita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 50 publications
2
13
0
Order By: Relevance
“…The theoretical process highlights the core driver of brand authenticity and the accelerator of creative performance. Although many scholars have emphasized the unique historical and cultural value of traditional catering brands ( Tian et al, 2018 ), to date, few studies have focused on addressing the brand decline and constructing a theoretical path of traditional catering brand inheritance, especially in remodeling from a new customer perspective rather than an enterprise perspective ( Li et al, 2019 ; He, 2008 ). Importantly, the critical leading factor of brand authenticity is placed in the present and the future, not just historical period ( Lu et al, 2015 ; Sims, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The theoretical process highlights the core driver of brand authenticity and the accelerator of creative performance. Although many scholars have emphasized the unique historical and cultural value of traditional catering brands ( Tian et al, 2018 ), to date, few studies have focused on addressing the brand decline and constructing a theoretical path of traditional catering brand inheritance, especially in remodeling from a new customer perspective rather than an enterprise perspective ( Li et al, 2019 ; He, 2008 ). Importantly, the critical leading factor of brand authenticity is placed in the present and the future, not just historical period ( Lu et al, 2015 ; Sims, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…Around the world, many traditional brands are struggling with their own decline ( Li et al, 2019 ). Similarly, in China, the time-honored brand is the best surviving centuries of business and handicraft competition after generations of inheritance, showing irreplaceable value.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it is widely agreed that culture provides potentially productive areas for brand development, researchers have suggested that most research is yet to address this historical culture's importance in brand development [38]. However, there have been discussions in the literature, like those of Li et al, (2019), that emphasize the discussion of cultural heritage on brand revitalization for traditional enterprises from the perspective of market management [42]. Further, some research does show that historical and cultural resources can provide new perspectives of understanding and can represent national culture in order to affect audience behavior [43].…”
Section: Brand Culturementioning
confidence: 99%
“…Considering the dynamic notion of competitive business settings, besides competitive offerings, it is prevalent that consumer's perception of the value changes over time. Therefore, given the importance of managing and developing BE, on sustainable performance of companies, in particular, brand sustainability of products [36,37], the present study will examine three key sub-dimensions of brand equity: Brand awareness, perceived quality, and prestige value to better understand the consequences of brand equity as one of the most valuable assets from consumers viewpoint.…”
Section: Brand Equity (Be)mentioning
confidence: 99%